Upaya Pengenalan Budaya Lokal Batik untuk Meningkatkan Kreativitas Siswa Madrasah Ibtidaiyah Pekalongan - Millatu Zulfa; Hidayatu Munawarah; Sofan Rizqi (Madako Elementary School, 2023)
The purpose of this research is to introduce the local culture of batik and increase the creativity of fifth grade students at MI NU Buaran Pekalongan through the local culture of batik. This type of research is field research with a qualitative descriptive analysis based on the philosophy of postpositivism. The results of this study explain that efforts to introduce batik culture to fifth grade students of MI NU Buaran before carrying out study tour activities are still not developed. Students are introduced to the batik collection at the batik museum which is exhibited in the exhibition hall. Not only typical Pekalongan batik, but batik from ancient times to today as well as batik from abroad. The creativity abilities of the fifth grade students of MI NU Buaran after this study tour have developed quite well. The 10 students who took part in the visit to the batik museum had different creativities. out of 10 children 9 children have well-developed creativity because they have fluency and flexibility in making batik works that have been done, but there is 1 student who has creativity that is quite well developed due to a lack of flexibility in creating batik works.